solve using procces of elimation
Stacey Warren - Expert brainly.com
Hey! We 've verified this expert answer for you, click below to unlock the details :)
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga.
Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus.
Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.
I got my questions answered at brainly.com in under 10 minutes. Go to brainly.com now for free help!
start by multiplying equation 1 by 5 and equation 2 by 5
then subtract to eliminate y
Not the answer you are looking for? Search for more explanations.
Ok thank you =D
give it a go
you need to multiply equation 1 by some number (call it A) and equation 2 by some other number (call it B) such that either the coefficients of x or y become the same.
so for x (for example) we need 3A = 10B
or for y, we need 2A = 5B
can you think of what A and B should B to make either of these two equal?
ok, lets say we want to eliminate y, then we need to find two numbers A and B such that:
2A = 5B
we could pick A=5 and B=2 to get:
2*5 = 5*2
so now if we multiply the first equation by 5 and the second one by 2 we get:
5(3x + 2y) = 5(-9) ==> 15x + 10y = -45
2(-10x + 5y) = 2(-5) ==> -20x + 10y = -10
now we have two equations where the coefficients of y are the same, so we can subtract one from the other to eliminate y.
do you know how to do that?
15x + 10y = -45 - equation 3
-20x + 10y = -10 - equation 4
equation 3 minus equation 4 will give us:
(15 - (-20))x = -45 - (-10)
(15 + 20)x = -45 + 10
35x = -35
x = -1
you can now substitute this back into either your first or second equation to find y.